PERTANGGUNG JAWABAN HUKUM PIDANA BAGI PELAKU PROSTITUSI ONLINE - Ipaldi, Muhamad Irpan; Amalia, Mia; Mulyana, Aji (Jurnal Dialektika Hukum, 2024)
One of the efforts used to tackle online prostitution activities is a criminal law policy approach through the formulation of criminal sanctions as a form of criminal responsibility for perpetrators of online prostitution. The provisions governing criminal penalties for users of online prostitution services result in the prevention of online prostitution itself not being optimal, so users of online prostitution services will feel safe and remain free to purchase services for their sole satisfaction, while this is contrary to various aspects of norms, especially legal norms in public. Therefore, it is necessary to reform criminal law, related to criminal liability for users of online prostitution services. So that it does not disturb the surrounding community.